The Ability of Neem Leaf Extract (Azadirachta indica) To Suppres The Populationof Brown Planthopper (Nilaparvata lugens) On Rice Plant - Martua S. Sianipar; Lucyana Jaya; Roynaldi Sinaga (Faculty of Agriculture, Pattimura University, 2020)
Brown Planthopper (Nilaparvata lugens) is the main pest of rice plants. Alternative controls such as the use of plant extract are being promoted. Neem is a botanical pesticide using for insect pests control, and its anti- bacterial, insecticide, fungicide and nematicide activities has been using as a pest control agent in plant cultivation. The experiment was carried out in the Greenhouse of Faculty of Agriculture, Universitas Padjadjaran. The experiment was designed in the Randomized Block Design with 5 treatment and 5 replications. The treatment tested was the concentration of neem leaf extract. The Mortality of brown planthoppers was calculated based on the number of dead brown planthopper compared to the initial number. The results of the experiment showed that neem leaf extract was able to suppress the brown planthopper population. The ectract treatment at the 10% of concentration for Neem plants can reduce the population of brown planthopper for about 78%.